ADP secretion and subsequent P2Y12 receptor signalling play a crucial role in thrombin-induced ERK2 activation in human platelets - Fälker, Knut; Lange, Danica; Presek, Peter (Thrombosis and Haemostasis, 2004)
Stimulating human platelets with thrombin induces the activation of the extra cellular signal-regulated kinase 2 (ERK2). We demonstrate that this effect is highly dependent on ADP secretion and P2Y12 receptor signalling. AR-C69931MX (10 µM), a specific antagonist of the Gi-coupled P2Y12 ADP receptor, inhibits ERK2 activation induced by thrombin. Antagonists of the Gq-coupled P2Y1 ADP receptor, A3P5P (500 µM) and MRS2179 (100 µM), have no effect. ADP and its more potent analogue 2-methylthio-ADP alone (both up to 100 µM) do not induce ERK2 activation. Furthermore, we show that the inhibitory effect of AR-C69931MX on ERK2 activation induced by 0.1 U/ml thrombin as well as on platelet aggregation can be bypassed by epinephrine (1 and 10 µM), whereas epinephrine alone has no effect. Epinephrine acts on platelets mainly via α2A-adrenergic receptors, which, like P2Y12 receptors, couple to inhibitory G proteins. In addition, 2-methylthioADP as well as epinephrine provoke ERK2 activation at a thrombin concentration that alone has no detectable effect (0.05 U/ml). Thromboxane A2 (TXA2), which, like ADP, is released by activated platelets, acts as a positive feedback mediator. Stimulating the Gq-coupled TXA2-receptor with U46619 (10 µM), which leads to ADP secretion and P2Y12 receptor dependent platelet aggregation, also induces P2Y12-related ERK2 activation. The inhibition of U46619-induced ERK2 activation and platelet aggregation by AR-C69931MX are also rescued by epinephrine. Pretreatment with aspirin inhibits ERK2 activation induced by 0.1 U/ml thrombin, but has no effect at high concentrations of thrombin. The combination of U46619 and thrombin, at concentrations which alone have no effect, provokes ERK2 activation, suggesting that thrombin and released TXA2 act synergistically. Our data indicate that both primary signalling through Gq, which evokes ADP secretion, as well as subsequent coupling via Gi by the P2Y12 receptor are required for ERK2 activation.
Keywords: Platelets; thrombin; ADP; P2Y12 receptor; ERK2